An applied paradigm for simple analysis of the lower limb kinematic chain in explosive movements: an example using the fencing foil attacking lunge. Issue 1 (1st January 2018) - Mulloy, Francis; Mullineaux, David R.; Graham-Smith, Phillip; Irwin, Gareth
Abstract: A simple method to quantify the kinematic chain in a propulsive task would facilitate assessment of athlete effectiveness. The study's aim was to assess if the kinematic chain distinguishes between skill levels. Fencers were separated into two groups based on attacking lunge ability (7 skilled; 8 novices). Rear leg 3D joint angular extension velocity magnitudes and timings, sword kinematics and rear leg kinetics were obtained in the propulsion phase of the attacking lunge. Skilled fencers obtained greater sword velocity (3.24 ± 0.24 m∙s−1 vs. 2.69 ± 0.29 m∙s−1; p = 0.02). The skilled group had a greater sequential kinematic chain of the hip, knee and ankle, demonstrated by significantly greater ankle angular velocity (9.1 ± 2.1 rad·s−1 skilled; 5.4 ± 2.9 rad·s−1 novice).  Ankle plantarflexion velocity showed a strong positive correlation with horizontal peak force ( r = 0.81; p < 0.01). The skilled group demonstrated greater horizontal impulse (1.85 ± 0.29 N·s·kg−1 skilled; 1.45 ± 0.32 N·s·kg−1 novice), suggesting greater effectiveness in applying the kinematic chain towards horizontal propulsion. Analysis of the kinematic chain, which was able to distinguish between skill levels in a propulsive task, is an effective and simple paradigm to assess whole limb contributions to propulsive movements.